A Vanitas em obras de arte contemporânea: um estudo iconográfico - Witeck, Ana Paula Gomes (2012)
This Master Degree Thesis aims to identify how a small set taken from a series of contemporary artworks, considered by some authors as "contemporary Vanitas" is characterized formal, symbolic and thematically, delving to evidence how the today s art can incorporate its historical past and especially the Vanitas traditional theme. The study, using an iconographic approach based on the method of Erwin Panofsky, primarily noted that the analyzed group of artworks, besides incorporating other themes with that of traditional Vanitas, showed a great formal distance from the ancient Vanitas paintings. The survey also verified that these artworks do not take the traditional Vanitas only by displaying the same symbolic motifs of the theme, but in fact, by the apprehension of its idea, which can be summarized as the confrontation between the man's vanity and the transience of his earthly life.